PENGARUH HARGA, KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN MJ ENAMEL - Woro Utari; M. Luthfi Alif Utama; Asep Heryyanto; Rudiatno (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2022)
The purpose of this study is to test and analyze the effect of Price, Product Quality and Service Quality on Customer Satisfaction. The sampling method uses Accidental Sampling. The number of samples used in this study are 60 customer respondents from MJ ENAMEL. Then an analysis of the data obtained by using quantitative data analysis. Quantitative data analysis assisted by the SPSS 21 Application program includes; validity and reliability test, normality test, multiple regression analysis, coefficient of determination analysis (R2), Descriptive analysis, Hypothesis F test and T test.Hypothesis Testing Results through the F test can be seen that the variable Price (X1), Product Quality (X2) and Service Quality (X3) simultaneously have a positive and significant effect on customer satisfaction (Y). Then the results of the t test show that Product Price and Quality partially have a positive and significant effect on the Customer Satisfaction variable. While the Service Quality variable partially does not significantly influence the Customer Satisfaction variable.